PID Control System on Air Levitation Tube - Ghazy, Maulana Irfan; Ma'arif, Alfian; Fauzan, Muhammad Fathan (Peneliti Teknologi Teknik Indonesia, 2024)
In the modern technological era, industries continuously seek to improve efficiency, speed, and safety in production processes, with control systems playing a vital role, especially in applications requiring high precision. One such application is air levitation systems, which enable contactless object positioning using controlled airflow. This research focuses on the design and implementation of a Proportional-Integral-Derivative (PID) control system for an air levitation tube, specifically aimed at maintaining the stable position of a ping pong ball within the tube. The system employs an ultrasonic sensor to measure the ball's position and a brushless motor, controlled via an Electronic Speed Controller (ESC), to regulate the airflow. The optimal PID parameters were determined through systematic tuning across various setpoints, yielding Kp = 1, Ki = 0.01, and Kd = 0.7, allowing the system to maintain stability and respond effectively to disturbances. The results demonstrate that the PID control system successfully regulates the ball’s position with minimal oscillation and fast response time. This achievement highlights the viability of PID-controlled air levitation systems not only for industrial use but also as educational tools in engineering and automation training. By integrating hardware and control algorithms into a practical setup, this study contributes to both technological development and enhanced pedagogical approaches in control engineering.